The Economic and Environmental Benefits of Partial Leasing of Agricultural Water Rights. Issue 11 (16th November 2021) - Khanal, Rajendra; Brady, Michael P.; Stöckle, Claudio O.; Rajagopalan, Kirti; Yoder, Jonathan; Barber, Michael E.
Abstract: Balancing out‐of‐stream water demands and ecological instream flows is a difficult challenge in watershed‐scale management. Many watersheds already experience acute and chronic water shortages during average runoff years and may face more frequent and severe droughts in some locations due to climate and demographic change. Water markets may mitigate the economic consequences of shortages, but their potential is limited by the prevalence of all‐or‐nothing irrigate‐or‐fallow crop water use strategies. Irrigation water generally provides diminishing returns for crop productivity, so it may be possible to reduce water application at the margin with only a small loss in crop production, creating water savings that could be leased for other uses. We explore this scenario by combining a crop growth and hydrology (CropSyst) model with an economic model of farm profits and water trading, and apply it to the Walla Walla Basin in Washington State. Our results suggest that partial leasing of water rights through a deficit‐irrigation strategy could economically benefit annual crop growers while meaningfully increasing water availability for stream flow augmentation. Key Points: Facilitating partial‐leasing markets can create a win‐win situation for both agriculture and the environment A variety of deficit‐irrigation strategies can be explored for facilitating partial water‐leases Benefits of partial‐leasing markets provide justification for investments in better consumptive use measure and monitoring